Mosquitoes (Diptera: Culicidae) wing morphometry comparison between Aedes sp., Culex sp. and Anopheles sp. of three departments in Peru (2024)
Arthropod-borne viruses (arboviruses) are significant emerging infectious disease threats due to their capacity to cause severe diseases in humans and their rapid geographic spread. Accurate genus and species identification of mosquitoes is crucial for public health, but it is challenging. To address these challenges, geometric morphometrics, which uses a landmark-based approach to analyze mosquito wing patterns, can be employed. For that reason, this study aims to describe the wing morphometry differences between Aedes sp., Culex sp., and Anopheles sp. mosquitoes from Piura, Madre de Dios, and Lima, Peru, based on location, genus, and sex. Using geometric morphometric analyses, including Generalized Procrustes Analysis (GPA), Principal Component Analysis (PCA), and Canonical Variate Analysis (CVA), we found subtle shape differences among genera, particularly in central landmarks. PCA indicated minimal shape variation in Anopheles sp. and greater variability in Aedes sp., while CVA demonstrated distinct wing shape characteristics for each genus and geographic differences. Gender-based analyses within Anopheles sp. suggested sexual dimorphism in wings. These results indicate significant morphometric differences among genera influenced by environmental or genetic factors, highlighting the potential of wing shape as a reliable feature for mosquito identification and differentiation across regions. However, more studies and statistical analysis needs to be done to conclude.